In-hospital outcomes after rotational atherectomy in patients with low ejection fraction. (4th July 2018) - Watanabe, Yusuke; Naganuma, Toru; Kawamoto, Hiroyoshi; Ishiguro, Hisaaki; Nakamura, Sunao
Abstract: Objectives. This study evaluated angiographic success and in-hospital outcomes of percutaneous coronary intervention (PCI) with rotational atherectomy (RA) in patients with low left ventricular ejection fraction (LVEF). Design. Between January 2010 and March 2014, 272 consecutive patients with heavily calcified lesions underwent elective PCI with RA. Of these, 33 patients had LVEF ≤35% (low LVEF group), whereas 237 patients had LVEF >35% (preserved LVEF group). The primary endpoint was angiographic success and in-hospital major adverse cardiac events (MACE). MACE included death from any cause, postprocedure onset MI, emergency coronary artery bypass grafting, and target vessel revascularization. The secondary endpoints were MACE and the components within 30days after PCI. The components of MACE were evaluated. Results. Angiographic success, defined as <30% residual stenosis with thrombolysis in myocardial infarction flow 3 at final angiography, was achieved in all patients without fatal complications. Intra-aortic ballon pumping (IABP) was used significantly more frequently in the low LVEF group compared with the preserved LVEF group (15.2% vs. 2.1%, p  = .003). There were no significant differences between groups regarding in-hospital and clinical outcomes within 30 days following PCI. Conclusion. If medications and mechanical support were appropriately performed, the angiographic success rate and in-hospital MACE rate of PCI with RA in patients with low LVEF could be expected to have good outcomes similar to those for patients with preserved LVEF.